Filmes e revestimentos ativos à base de amido e bioativos de Spondia purpurea para aplicação em manga minimamente processada - Rodrigues, Francisco Alessandro Marinho (2018)
Packaging makes it possible to protect food against various agents, preventing or delaying undesirable chemical, physical and biological processes that may affect the quality of the product. In this context, the use of functional packaging that performs an antimicrobial and antioxidant function may help to maintain quality and inhibit the microbiological deterioration of food. Based on this, this work evaluated the properties of starch films and phenolic actives of Spondia purpurea stem bark to protect minimally processed "Tommy Atkins" mangoes. The initial stage of the work consisted in the extraction and characterization of Spondia purpurea starch as the polymeric matrix of the films and coatings. The starch presented a yield of 15.42%, amylose content of 44.4 ± 1.7%, molar mass in the order of 105 g mol-1 and polydispersity of 1.5, good thermal stability and crystallinity standard of type A. The chemical profile of the hydroalcoholic extract of the stem bark of S. purpurea was determined by UPLC-QTOF-MS, and 35 secondary metabolites were tentatively identified, being mainly 17 compounds belonging to the class of flavonoids. The extract presented total phenolic content in gallic acid equivalents of 523.25 mg EAG g-1 of extract and its antioxidant activity was evaluated through the percentage of free radical DPPH· inhibition, which presented an IC50 of 5.85 μg mL-1. The antimicrobial activity of the extract showed inhibition action (MIC) in the evaluated microorganisms, E. coli, S. enterica, S. aureus and L. monocytogenes and of bactericidal action, with the concentrations tested in S. aureus and L. monocytogenes. The films developed with different phenolic extract contents of Spondia purpurea (0% to 20%) showed that the chemical composition of the extracts influenced the mechanical parameters, showed significant variation in tensile strength (σ), elongation (ε) and modulus of elasticity (Y) as the extracts content increased, showing an additional plasticizer action offered by the polyphenolic components present in the extracts. This observation was reinforced by the decrease in Tp values (161.4 to 149.6 °C) of the main endothermic event in the DSC thermograms of the films. They also presented water vapor permeability values between 2.78 and 2.14 g mm kPa-1 h-1 m-2 that were not significantly influenced by the content of phenolic extracts. The content of the soluble mass of the films ranged from 14.5% to 33.8%, indicating an increase in the solubility of the material as the extracts content increased. The application of the coatings, from 0% to 20% of phenolic extracts in minimally processed mangoes, had a protective effect on ascorbic acid levels and maintained the rates of complex sugars in the mangoes, observed by the analysis of soluble solids content. The highest concentrations of extracts allowed significant changes in color parameters (L*C*h*) over the 10 days of storage. In general, coatings containing 5% and 10% presented as more viable options for application in the market due to the lower color variations and contribute to the maintenance of components indicative of the quality of the minimally processed mango samples when compared to the control sample.